PENYULUHAN PENCEGAHAN KANKER PAYUDARA DI LAPAS KLAS II A PONTIANAK - Zam Zami (Jurnal Buletin Al-Ribaath, 2017)
Nowadays, cancers which most happened is breast cancer. The victims of this disease happened to the women. It even can cause death. However, not many people who know how to characterize these symptoms and how to face it. So, it is necessary to conduct the workshop to prevent breast cancer. Lapas Klass A II Pontianak is the prison for women. We feel they need to get the workshop about it as one of their activity in that prison to make them have new knowledge about health. So they can increase their awareness and can prevent, do early detection and treatment by themselves. This knowledge not only to themselves but also be able to help people around to avoid breast cancer occur. Keywords: Breast cancer, the prevention, workshop